Determinação sequencial de cromo, tálio, cádmio,chumbo, cobre e antimônio em concentrado polieletrolítico para hemodiálise por voltametria de redissolução através de um gradiente de pH - Schneider, Alexandre Batista (2010)
The sequential voltammetric determination of chromium, thallium, cadmium, lead, copper and antimony, present as contaminants in dialysate concentrates (CPHD), is presented herein. These concentrates contain a very high chloride concentration (ca. 3.8 mol L-1), which makes difficult the direct analysis, without pretreatment, by many analytical techniques, like atomic absorption spectrometry and chromatography. The experimental conditions were varied in order to improve the peak resolution, selectively and sensitivity. The method is based on the gradual decrease on the pH of the solution present in the voltammetric cell, so that, the sequential determination of the analytes was possible. At pH 6 6.2, Cr determination was carried out with DTPA by catalytic adsorptive stripping voltammetry (CAdSV). Afterwards, the pH was adjusted at 4.8 ± 0.2 to determine thallium by anodic stripping voltammetry (ASV). At this pH, DTPA is non interfering specie for Tl-determination and, additionally, it masks the main interfering species for thallium (lead and cadmium). Cadmium, lead and copper were assayed by ASV after setting the pH to 1.5 ± 0.5. Under these conditions, DTPA releases these three metallic species from the previously built complexes, so that they behave as free species to react on the HMDE-surface. By setting with HCl the pH to values around zero antimony was assayed by ASV. At this acidity and in presence of high chloride concentrations antimony can be assayed with high sensitivity. The method was used for analysis of commercial samples of CPHDs and the found concentration varied from < LD until 140 Ug L-1.